Sedimentary microfacies and organic geochemical characterization of mudstones in the Keluke Formation in northeastern Qaidam, China. (4th July 2017) - Liu, Xiaoguang; Li, Sanzhong; Zhong, Jianhua; Li, Yong; Liu, Xuan; Ni, Liangtian; Liu, Shengxin; Dong, Shoutao; Guo, Runhua; Lan, Haoyuan; Sun, Wenjun
Abstract : During the Early Carboniferous, the northeastern Qaidam Basin probably formed in an active continental margin setting. Due to marine regression after the late Early Carboniferous, the marginal shelf began to receive more terrestrial clastic sediments, and alternating occurrence of carbonates and siliciclastics characterized this region. Consequently, shales or mudstones with considerable thickness were deposited in the Upper Carboniferous, especially in the Keluke Formation. In order to illuminate a more accurate sedimentary environment of shales and further evaluate the shale gas potential, multidisciplinary traditional methods were conducted including rock core examinations and laboratory analysis. Results reveal that the sedimentary microfacies of shales in the Keluke Formation can be divided into the upper shoreface, the lower shoreface, and the upper to transition offshore. These microfacies developed on a homoclinal carbonate ramp with a gentle slope. The thickest succession of mudstone develops in the lower shoreface, which is a counterpart with the lagoonal setting of a stationary hydraulic system. The quartz content of shale samples ranges from 30% to 66% and clay minerals from 24% to 43% by bulk compositional analysis, which indicates the content of brittle minerals and shales fissility to some extent. The total organic carbon content ranges from 0.5% to 7.6% by weight, with an average value of 2.69% in ZK1‐1 and 1.11% in ZK3‐2, indicating abundant organic matter richness. The kerogen is mainly of type II, which indicates that source for the organic matter is a mixture of higher terrestrial plants and acquatic organisms. The vitrinite reflectance ranges from 1.22% to 1.55%, indicating a moderate to high thermal maturity. Three types of pores are recognized in the shales, including organic pores, intrapartical pores, and interparticle pores. The significance of this work emphasizes two aspects. First, it gives a more detailed classification of sedimentary environment of the mudstone succession; second, it acquires the preliminary subsurface data regarding to the shale gas potential evaluation.